Pathology of cutaneous blastomycosis in a cat - Vetnizah Juniantito; Eva Harlina; . Jumari; Vici Eko Handayani; Iis Ismawati (ARSHI Veterinary Letters, 2020)
Cats are common as pet animals in Indonesia and live in close vicinity of human neighborhood, which make them potential for transmitting diseases to human. Blastomycosis is infectious disease caused by Blastomyces spp yeast. Here we describe morphopathology of blastomycosis found in skin of a Persian Cat. Grossly, the lesion were characterized by ulcerated wounds and multiple subcutaneous small nodules (2-5 mm in diameter) in the base of tail. Skin biopsy was made and further processed for histopathology. Microscopically, the lesion consist of epidermal necrosis, dermatitis, with coalescing dermal granulomatous inflammation, characterized by epitheloid and foreign type giant cells infiltrates. Numerous spherical-shaped structures and pseudohyphae which are Periodic Acid Schiff (PAS)-positive consistent with yeast morphology were found within the granulomas; morphology is also consistent with Blastomyces spp yeasts. Conclusively, multiple granulomatous dermatitis with evidence of Blastomyces yeasts is a hallmark of cutaneous blastomycosis. Exposure to Blastomyces spp yeast may possess infection threat to pet owners.